Effect of Visual Attention Areas on the Objective Video Quality Assessment - Regis, Carlos D. M.; Cardoso, José V. M.; Alencar, Marcelo S. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
The objective assessment of video quality is an important area of research for the validation of video systems, and new algorithms are always in demand. Experiments indicate that the inclusion of characteristics of the human visual system into the objective metric, such as visual attention, improves the evaluation. This paper presents a new approach to evaluate the video quality based on an estimate of the local visual attention, using the structural similarity index. This approach is compared with three classical objective metrics: PSNR, SSIM and MS-SSIM, by means of the Pearson linear and Spearman rank-order correlation coefficients. The videos are submitted to several types of distortions, such as blocking, blurring and salt & pepper noise. The results indicate that the proposed approach presents good correlation with the subjective scores, for videos that contain blurring and blocking degradations.